KEPUASAN KONSUMEN TERHADAP LAYANAN GOJEK MELALUI CITRA MEREK DAN HARGA SEBAGAI VARIABEL INTERVENING - Sri Ndaru Arthawati (Jurnal Cakrawala Ilmiah, 2023)
The purpose of this study is to determine the influence of brand image and price to user satisfaction through the decision to use as intervening variable. Quantitative analysis method is used in this resecrh. Methods of data collection is using questionnaires with 100 respondents. Sampling technique is using accidental sampling method with criteria of respondents is students of Sultan Ageng Tirtayasa University who have used Go-Jek more than 3 times. The data used in this study is the primary data. Data analysis is using path analysis with SPSS program version 22 and Sobel Test. The statistical test shows that the brand image has a positive and significant impact on user satisfaction, but the price has no significant and positive effect on user satisfaction. Brand image and price variable have positive and significant influence on decision to used the service. Path analysis shows that the decision to use the service as intervening variable can not mediate the relationship of brand image and price to satisfaction.